CEO attributes, board independence, and real earnings management: Evidence from Nigeria - Auwalu Musa; Rohaida Abdul Latif; Jamaliah Abdul Majid (Cogent Business & Management, 2023)
Motivated by agency conflicts of real earnings management and upper echelons in CEO demographic characteristics, this study examines the effect of CEO attributes on real earnings management and addresses the question of whether the presence of an independent board ensures accurate and reliable financial reporting practice. The study also examines the extent to which independent boards moderate the relationship between CEO attributes and real earnings management. Using a sample of 292 observations from Nigeria, an emerging market, from 2018 to 2021, a feasible generalized least square (FGLS) regression model was used to analyze the data. The authors also consider alternative measures of real earnings management. Our results demonstrate that CEO financial expertise, compensation, and CEO nationality reduce real earnings management and improve the financial reporting quality. Accordingly, the results show that independent directors on the board strengthen the CEO's ability to reduce likely earnings manipulation. However, we find that the presence of a female CEO does not mitigate real earnings manipulation, but that the presence of independent directors enhances the ability of female CEOs to reduce earnings manipulation and produce reliable financial reports. Our results are robust and may have implications for regulators, shareholders, managers, and researchers because it shows that CEO attributes and the presence of independent directors on the board are associated with higher earnings quality.
Keywords: 650; CEO attributes; financial reporting; independent board; real earnings management; upper echelon theory